Highly Stable and Ultrahigh‐Rate Li Metal Anode Enabled by Fluorinated Carbon Fibers. Issue 4 (29th December 2020) - Xia, Shuixin; Zhang, Xun; Luo, Lingli; Pang, Yuepeng; Yang, Junhe; Huang, Yizhong; Zheng, Shiyou
Abstract: The advanced energy storage of an Li metal substituted for graphite anode can provide a significant enhancement in a battery's energy density. Nevertheless, the practical implementation of metallic Li has seriously been fettered by the notorious Li dendrite growth and the huge volumetric variation of Li metal inducing poor cycling performance and safety concerns. In this regard, constructing a robust SEI layer combined with a 3D host to stabilize the Li metal is strongly in demand. Herein, a highly stable hosted Li with an LiF dominated SEI has successfully been achieved through metal‐free fluorinated carbon fibers (FCF) with strong lithiophilicity. The metal‐free design is cost‐effective and can retain the energy density of the Li metal, minimizing the unnecessary energy sacrifice from the extra high gravimetric density lithiophilic sites. The FCF hosted Li delivers a promoted high Coulombic efficiency, homogeneous Li deposition, and ultrahigh rate stable cycling over 1000 cycles at 20 mA cm −2 with a much lower voltage polarization (≈220 mV). Moreover, half cells coupled with LiNi0.8 Co0.1 Mn0.1 O2, sulfur or even thick LiCoO2 cathode demonstrate superior rate performances and enhanced cycling stability even under a lean electrolyte. This work proves the feasibility of FCF hosted Li for practical usage and provides a novel approach toward cost‐effective and high performance lithium metal batteries. Abstract : A highly stable hosted Li with LiF‐dominate solid electrolyte interlayer (SEI) has been fabricated, which delivers a promoted high Coulombic efficiency, homogeneous Li deposition and ultrahigh‐rate stable cycling over 1000 cycles at 20 mA cm −2 with a lower voltage polarization. Moreover, half cells with LiNi0.8 Co0.1 Mn0.1 O2, sulfur or even thick LiCoO2 demonstrate enhanced cycling stability even under lean electrolyte.